Geochemical characteristics of tourmaline in Longqiao skarn Fe deposit in LYRMB, Eastern China: Constraints on magmatic-hydrothermal processes - Shasha Liu; Yu Wang; Mingguang Sun; Zhuang Zhao; Hui Luo; Muhammad Hafeez; Linzi Li; Xiaoyong Yang; Jiandong Sun; Bangguo Ou (Journal of Geochemical Exploration, 2026)

Evaluation of gene markers invA, phsB, and tviA for detection of Salmonella Typhi by SYBR Green TM real-time PCR assay in clinical samples - Muhammad Luqman Qadir; Samreen Arshad; Nazim Hussain; Saima Younas; Rabia Arooj; Ahmer Bin Hafeez (Molecular Biology Reports, 2026)

Research knowledge in wolfberry (Lycium spp.) diseases: pathogen diversity, diagnostics, and integrated management under climate change - Olaide Ayodele Oladeji; Muhammad Naeem; Hafeez ur Rehman; Moses Akintayo Aborisade (Crop Protection, 2026)

Zircon and apatite geochemical and isotopic constraints on magma fertility and magmatic evolution of porphyry CuAu mineralization at the Ting Darigun prospect, Chagai Belt, Western Pakistan - Muhammad Hafeez; Xiaoyong Yang; Ahmed Shah; Zahra Abbasi; Salman Ahmed Khattak; Ibrar Khan (Lithos, 2026)

Recent advances in electrochemical ion separation: Materials, mechanisms and sustainable applications for water and resource recovery - Luqman Ali; Abdul Majid Khan; Muhammad Usman Hameed; Saleem Raza; Liguo Shen; Imran Shakir; Muhammad Hafeez (Desalination, 2026)

A metal-organic framework-based multifunctional film for active food preservation and visual spoilage monitoring - Muhammad Junaid Khan; Muhammad Rehan Islam; Farooq Hafeez; Yinyin Wang; Yunlei Xianyu (Chemical Engineering Journal, 2026)

High-resolution ambient noise tomography of the Dabie Orogenic Belt, China: New insights into crustal structure and tectonic evolution - Muhammad Imran Hafeez Abbasi; Jikun Feng; Huajian Yao; Song Luo; Xin Liu (Tectonophysics, 2026)

Enhancing resource productivity and system sustainability on the Qinghai-Tibetan Plateau: a type-temporal-spatial coupling approach for forage-livestock balance - Jing Zhang; Nurlan Serekpayev; Muhammad Usman; Naeem Ahmad; Muhammad Bilal Hafeez; Qingping Zhou; Fujiang Hou; Zhibiao Nan (Plant and Soil, 2026)

Editorial Expression of Concern: Taurine decreases arsenic and microplastic toxicity in broccoli (Brassica oleracea L.) through functional and microstructural alterations - Shahar Yar; Muhammad Arslan Ashraf; Rizwan Rasheed; Umer Farooq; Arslan Hafeez; Shafaqat Ali; Mudassar Shahid; Pallab K. Sarker (BioMetals, 2026)

Large-scale microtremor analysis and lineament mapping for evaluating geological hazards in reservoir-induced seismicity regions: The case history of Kenyir Geopark - Susie Cahyanti Tasman; Neeran Niraj; Muhammad Noor Hisyam Jusoh; Abdul Halim Abdul Latiff; Siti Nur Fathiyah Jamaludin; Muhd Nur Ismail Abdul Rahman; Rudiyanto; Muhammad Afiq Md Ali; Muhamad Zaki Zulkifli; Yuzwan Mohamad; Kee Soo Chen; Fawwaz Azfar Abd Ghafar; et al. (Journal of Applied Geophysics, 2026)

A multi-dimensional accounting framework to resolve the grassland-livestock paradox on the Qinghai-Tibetan Plateau - Jing Zhang; Naeem Ahmad; Muhammad Bilal Hafeez; Muhammad Usman; Qingping Zhou; Fujiang Hou; Zhibiao Nan (Global and Planetary Change, 2026)

Deciphering the role of potato peel on sunflower hybrids growth, photosynthesis, osmoregulation, oxidative defense and ion uptake under salinity - Sundas Fatima; Aasma Tufail; Muhammad Bilal Hafeez; Samreen Nazeer; Noreen Zahra; Fatima Latif; Sabina Asghar; Muhammad Ahsan; Muhammad Hamza; Muhammad Zubair Akram (Biocatalysis and Agricultural Biotechnology, 2026)

Evaluation of Larvicidal Potential of Nepeta cataria and Cymbopogon nardus Essential Oils Against Aedes aegypti - Iqra Shafeeq; Sammina Mahmood; Adeel Sattar; Qamar Niaz; Mian Abdul Hafeez; Muhammad Ilyas; Muhammad Shahid Mahmood (Acta Parasitologica, 2026)

Comparative genome-wide analysis and characterization of galactinol synthase (GolS) gene family in diploid and tetraploid cotton species - Umm e Abaida Noor; Muhammad Shaban; Muhammad Abubakkar Azmat; Saman Arshad; Abdul Hafeez; Kamran Javed (Biologia, 2026)

Evaluation of host suitability and larval instar effects on the reproductive potential of entomopathogenic nematodes against lepidopteran pests - Hina Safdar; Sumaira Maqsood; Salman Ghuffar; Aftab Ahmad; Muhammad Hafeez; Hifza Safdar; Tauseef Anwar; Huma Qureshi; Hossam S. El-Beltagi; Ibrokhim Ismoilov; Feruza Tukhtaboeva; Nazih Y. Rebouh; et al. (Crop Protection, 2026)

Next-generation thermal management systems for lithium-ion batteries: Enhancing the performance and safety in electric vehicles - Zahid Bashir; Riaz Hussain; Hafeez Khoharo; Jarrar Ali Jaffri; A.L. Saroj; Shahid Bashir; Jeyraj Selvaraj; Muhammad Shakeel Ahmad (Journal of Environmental Chemical Engineering, 2026)

Effects of legume-grass mixtures and systematic pasture management practices on forage yield, nutritive quality and resource use efficiency in an arid region - Muhammad Bilal Hafeez; Weiqi Jiang; Lan Li; Jiao Ning; Adilbek Nogayev; Shanning Lou; Shree Prakash Pandey; Fujiang Hou (Field Crops Research, 2026)

Sewage Sludge-Mediated Microplastic Transfer to Agroecosystem: A Comprehensive Review on Detection, Fate and Ecological Impacts - Muhammad Tariq Khan; Masroor Waliullah; Zohaib Abbas; Saba Hafeez; Mohammad Bhuyan; Nasrin Akhter; Iqbal Ahmad; Asim Nawab; Mushtaq Ahmad; Yanbo Zhou; Md Faysal Hossain (Water, Air, & Soil Pollution, 2026)
Microplastic (MP) pollution has become a significant environmental concern due to its persistent nature and toxic environmental effects. MPs pose threats to the aquatic and terrestrial environment by impacting plant habitats and altering soil properties. Wastewater treatment plants (WWTPs) are one of the most prominent channels for MP pollution in both aquatic and terrestrial ecosystems. MP particles separated during various treatment processes are trapped in the sludge and subsequently enter the terrestrial agroecosystem when sludge is used as fertilizer. In addition, sludge incineration releases tiny MP particles into the atmosphere. Although MPs have been extensively studied in aquatic environments, limited studies are available regarding their transport to agricultural ecosystems and the pathways through which they pose risk to food security and soil fertility. This review aims to evaluate the prevalence of MPs within sewage sludge and their subsequent translocation into terrestrial agroecosystems. A critical investigation has been carried out to address the challenges in detecting MPs in complex sludge samples to provide guidance for developing standardized and widely accepted methodologies. Furthermore, the impacts of MPs on soil fertility and biota were assessed and investigated from the perspective of agricultural production. This review aims to compile evidence of the presence and transport of MPs through sewage sludge applied to agricultural lands and help policymakers and environmentalists in developing viable strategies to protect agricultural land from MP pollution. Graphical Abstract

Geochemical and petrographic insights into the Lumshiwal Formation (NW Himalayas): implications for provenance, paleoclimate, and economic potential - Syed Nohman Gilani; Muhammad Saleem Mughal; Khawaja Umair Majeed; Hammad Tariq Janjuhah; Yongzhi Wang; Muhammad Atif Bilal; Ahmer Bilal; Syed Wajee-Ul Hassan Gillani; Muhammad Hafeez (Carbonates and Evaporites, 2026)

Application of biogas slurry abate Pb metal uptake and oxidative stress in maize (Zea mays L.) by modulating seedling emergence, antioxidant defense, and root structural–functional traits - Hafeez ur Rehman; Athar Mahmood; Muhammad Shahbaz; Zubair Aslam (BioMetals, 2026)

AcrAB-NodT overexpression drives envelope destabilization and metal sensitivity in Caulobacter vibrioides - Muhammad Shahid Mehmood; Yohana Amos; Muhammad Ali Abid; Ali Shan Hafeez; Naseeb Danaf (Archives of Microbiology, 2026)

Evaluation of the hepatoprotective activity of the methanolic extract of Cotinus coggygria - Shahzad Kamran; Sairah Hafeez Kamran; Mohsin Ahmad Ghauri; Ali Raza; Muhammad Ajaib (Advances in Traditional Medicine, 2026)

Sexual Dimorphism of Dendritic Spine Plasticity in the Cortex of Adolescent Mice - Fujian Qi; Yanli Ran; Guodong Zhu; Wancong Ding; Xing Gao; Junru Liu; Muhammad Tariq Hafeez; Huatai Xu; Shengxiang Zhang (Neuroscience Bulletin, 2026)

Spatial distribution of heavy metals and ecological risk assessment in Sea buckthorn across high-mountain landscapes of HKH ranges, Gilgit-Baltistan, Pakistan - Kamran Ali Khan; Faridullah Faridullah; Adnan Ahmad Tahir; Muhammad Irshad; Shaxina Tuyg’unovna Shukurova; Farhan Hafeez; Arshad Mahmood Abbasi (Environmental Geochemistry and Health, 2026)

Retraction Note: Do entrepreneurial orientation and intellectual capital influence SMEs’ growth? Evidence from Pakistan - Muhammad Ghazanfar Abbas; Zhuquan Wang; Hafeez Ullah; Muhammad Mohsin; Hasnain Abbas; Memon Rafait Mahmood (Environmental Science and Pollution Research, 2026)

Soil type regulates the development and insecticide susceptibility of Spodoptera frugiperda by modulating maize growth and nutritional content - Shi-Wen Deng; Mohammed Esmail Abdalla Elzaki; Wei Liang; Muhammad Hafeez; Wan-Ting Li; Rui-Long Wang (Pesticide Biochemistry and Physiology, 2026)

Evaluation of Thermal Comfort and Adaptive Responses of Secondary School Students in Naturally Ventilated Classrooms in the Tropical Savannah Climate of Nigeria - Tajudeen Dele Mustapha; Ahmad Sanusi Hassan; Muhammad Hafeez Abdul Nasir (Energy and Buildings, 2026)

Heavy Metals Bioaccumulation in Riparian Vegetation: A Multi-Species Biomonitoring Framework Using Total X-Ray Reflection Fluorescence Spectroscopy - Shakeel Ahmed Talpur; Simonetta Cristina Di Simone; Aziz Ahmed; Hafeez Ahmed Talpur; Muhammad Yousuf Jat Baloch; Francesco Stoppa; Luigi Menghini; Beatrice Maria Sole Giambastiani; Gianluigi Rosatelli (Environmental Processes, 2026)
Heavy metal contamination in Mediterranean riparian ecosystems presents serious risks to biodiversity and human health, requiring innovative biomonitoring methods for polluted watersheds. This study developed a comprehensive biomonitoring framework for an industrially impacted Mediterranean river basin, with approximately 100,000 tons of contaminated waste in landfills from decades of metallurgical processing. We investigated heavy metal bioaccumulation patterns in five taxonomically diverse native riparian species ( Equisetum arvense , Laurus nobilis , Rubus ulmifolius , Sambucus nigra , and Salix alba ) across contaminated and reference sites using Total Reflection X-ray Fluorescence (TXRF) spectroscopy. TXRF was validated against Inductively Coupled Plasma Atomic Optical Spectroscopy (ICP-AOS) using standard reference materials, demonstrating superior sensitivity for trace element detection in plant matrices. Heavy metal concentrations varied significantly among species and sites in riparian vegetation, with Fe (23.14 ± 5.21 mg/kg), Mn (2.74 ± 0.89 mg/kg), and Cr (3.33 ± 1.12 mg/kg) showing the highest accumulation. Laurus nobilis appeared as a multi-metal hyperaccumulator with the highest Pollution Load Index (PLI = 2.67) and exceptional accumulation of Cr (14.74 mg/kg) and Fe (63.64 mg/kg). Statistical analysis (Kruskal-Wallis test, p < 0.05) confirmed that Mn and Cr represented primary anthropogenic pollutants, with contaminated sites showing 2.20-fold and 1.92-fold increases, respectively. Principal Component Analysis revealed distinct co-accumulation networks, with Fe-Cr-Ni-Cu forming synchronized uptake mechanisms, while Mn operated independently. Biogeochemical ratio analyses (Fe/Zn, Cu/Mn) provided sensitive contamination indicators, detecting physiological stress beyond simple concentration measurements. Results support species-specific phytoremediation strategies aligned with UN Sustainable Development Goals, with Laurus suitable for multi-metal extraction and Equisetum for Mn-specific remediation, advancing sustainable environmental management in industrially impacted Mediterranean watersheds.

Financial technology and nuclear energy development: the moderating role of institutional quality in driving a sustainable future - Chuan Zhang; Mian Gohar Rahman Zafar; Muhammad Hafeez; Nie HongDi (Environment, Development and Sustainability, 2026)

Unraveling the Genetic Diversity of Lernaea Parasites Infecting Carp Through 18 S rRNA Gene Analysis - Farzana Abbas; Muhammad Hafeez-ur-Rehman; Farzana Ashraf (Acta Parasitologica, 2026)

Tectonic and metallogenic processes along the east Tethyan metallogenic domain (Lhasa-southern Tibet, Kohistan island arc and Chagai magmatic belt): a perspective review - Muhammad Hafeez; Xiaoyong Yang; Ahmed Shah; Ibrar Khan; Zahra Abbasi; Salman Ahmed Khattak; Gendenjamts Baatar (International Geology Review, 2026)

Multifunctional Mg-MOF-74@Carvacrol/Chitin nanofiber-based nanocomposite film for enhanced food packaging - Muhammad Junaid Khan; Muhammad Rehan Islam; Farooq Hafeez; Chunyan He; Jun Zhang; Yunlei Xianyu (Chemical Engineering Journal, 2026)

Genetic Innovations in Soybean: Key Genes Driving Salinity Tolerance - Muhammad Hafeez Ullah Khan; Jabar Zaman Khan Khattak; Ali Muhammad; Ehsan Ali; Sajjad Ali; Shah Fahad; Xianzhong Feng (Journal of Plant Growth Regulation, 2026)

Unveiling the synergistic potential of nucleopolyhedroviruses and insecticides against Helicoverpa armigera Hübner (Lepidoptera; Noctuidae) - Muhammad Jafir; Jam Nazeer Ahmad; Samina Tanwir; Muzamil Abbas; Faisal Hafeez; Muhammad Azeem Sabirb; Abdul Rehman; Abdulrahman S. Aldawood (Journal of Plant Diseases and Protection, 2025)

Effect of Fagonia Indica and Garlic Extract On Alternaria Alternata and Post-harvest Quality of Tomato Fruit During Storage - Sameer Lal; Ghulam Khaliq; Abdul Hafeez Mastoi; Asif Irshad; Muhammad Abuzar Jaffar; Lawang Khan; Noor Muhammad (Journal of Crop Health, 2025)

Prevalence in Relation to Risk Factors of Babesia Bigemina in Bovines of Punjab (Pakistan) - Muhammad Wahab; Mian Abdul Hafeez; Faiza Aslam; Rimsha Farooq; Syeda Anam Sarwar; Waqas Ahmad; Liaqat Ali; Adeel Sattar; Waseem Khan (Acta Parasitologica, 2025)

Salinity‐induced variations in growth performance, stress biomarkers and biochemical profiles of striped catfish ( Pangasianodon hypophthalmus , Sauvage, 1878) - Muhammad Nouman Riaz; Muhammad Hafeez‐ur‐Rehman; Hamda Azmat; Shahid Mehmood (Journal of Fish Biology, 2025)
Environmental salinity affects the growth, survival rate and physiological functions of fish. In this study, the effects of salinity stress on Pangasianodon hypophthalmus (Sauvage, 1878) fingerlings were examined over a 90‐day period. After acclimatization, a total of 300 P. hypophthalmus fingerlings were randomly assigned into three replicates and divided into five treatment groups with salinity levels of 0‰, 6‰, 12‰, 18‰, and 24‰ and with a stocking density of 20 fish per aquarium. After 90 days, the final weight, weight gain, weight gain percentage and specific growth rate significantly ( p p p p p p p p p p P. hypophthalmus in inland saline groundwater is 12‰, which ensures the maximum survival rate.

Zinc-based nanoparticles improved the growth, chlorophyll, osmoregulation and ions relations of sunflower under combined shade and drought stress - Maria Tariq; Aasma Tufail; Muhammad Bilal Hafeez; Mafia Shoukat; Naeem Ahmad; Shahid Iqbal; Maqsood ul Hussan; Tayyaba Tariq; Muhammad Kamran; Muhammad Ahsan; Fahd Rasul; Noreen Zahra (Biocatalysis and Agricultural Biotechnology, 2025)

Environmental Concern and Digital Engagement as Drivers of Circular Product Buying Intention in Malaysia: an Integrated S-O-R, TPB, and DOI Perspective - Husam Ahmad Kokash; Mst. Nilufar Ahsan; Muhammad Haroon Hafeez; Amira Naqeeb Khattak; Saif Ahmed; Syed Shah Alam (Circular Economy and Sustainability, 2025)

Sustainable Fruit Production: Enhancing Technical Efficiency and Climate Resilience in Apple Orchards - Yi Wang; Abida Hafeez; Pomi Shahbaz; Shamsheer ul Haq; Muhammad Nadeem (Applied Fruit Science, 2025)

Melatonin-mediated regulation of nitrogen metabolism and photosynthesis alleviates nitrate stress in tobacco (Nicotiana tabacum) - Abdul Hafeez; Zhengping Yao; Muhammad Junaid Rao; Zonghang Li; Muhammad Shaban; Zongmin Mou; Yongmei Li; Erqiang Zhao; Yi Xu; Suiyun Chen; Dake Zhao (Journal of Hazardous Materials, 2025)

Integrated multidisciplinary analysis of snowfall, freezing risks, and territorial resilience: a case study of the Wilaya of Batna, Algeria - Yahyaoui Habibi; Sami Guellouh; Billel Touati; Abdelwahhab Filali; Zizhan Zhang; Sidao Ni; Risheng Chu; Fouzi Bellalem; Fatima Baala; Houssam Meziani; Muhammad Imran Hafeez Abbasi; Ali Athamena (Mediterranean Geoscience Reviews, 2025)

Citrulline Reduces Copper Toxicity in Sunflower (Helianthus annuus L.) by Modulating Photosynthesis, Osmoregulation, Redox Homeostasis, and Nutrient Relations - Arslan Hafeez; Rizwan Rasheed; Muhammad Arslan Ashraf; Iqbal Hussain (Journal of Soil Science and Plant Nutrition, 2025)

Mitigating Terminal Drought in Chickpea (Cicer arietinum L.) Using Organic Manures; Effects on Yield, Potassium Uptake and Antioxidants Activity - Malik Muhammad Yousaf; Azra Yasmeen; Shadia Hama Salih Kareem; Muhammad Arif; Hesham F. Alharby; Hameed Alsamadany; Yahya M. Alzahrani; Amnah M. Alamri; Ammara Latif; Hafeez ur Rehman (International Journal of Plant Production, 2025)

Thiram-driven XBP1 and CHOP pathways orchestrate ER stress and avian tibial dyschondroplasia via metabolic inflammatory axis - Shah Nawaz; Muhammad Farhan Rahim; Khodja Salaheddine; Hafeez Ur Rehman; Chuxian Quan; Yuanyuan He; Md.F. Kulyar; Jiakui Li; Quan Mo (Pesticide Biochemistry and Physiology, 2025)

Acetylsalicylic acid and cancer: updates on the new potential of a nature-inspired drug - Abdur Rauf; Ahmed Olatunde; Md. Rezaul Islam; Zubair Ahmad; Nabia Hafeez; Hassan A. Hemeg; Muhammad Imran; Mohammad S. Mubarak; Giovanni Ribaudo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Seed Pre-treatment with Thiourea Improves Physiological and Metabolic Adaptation to Booting Stage Salinity in Wheat - Azka Saleem; Mehwish Rubab; Maria Abubakar; Ali Raza; Amnah M. Alamri; Hesham F. Alharby; Hameed Alsamadany; Yahya M. Alzahrani; Muhammad Waqas; Hafeez ur Rehman (Journal of Crop Health, 2025)

Evaluation of entomopathogenic fungi and nematode species for eco-friendly management of fall armyworm, Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) - Usama Saleem; Muhammad Asrar; Dilbar Hussain; Faisal Hafeez; Muhammad Sohail Qadir (International Journal of Tropical Insect Science, 2025)

Adaptive divergence in Ostrinia furnacalis: Diet-based fitness specification across wild, domestic and hybrid populations - Aleena Alam; Sohail Abbas; Faisal Hafeez; Muhammad Shakeel; Arzlan Abbas; Khalid Ali Khan; Hamed A. Ghramh; Jamin Ali; Adil Tonğa; Rizhao Chen (Crop Protection, 2025)

Alleviating cadmium-induced stress in maize: the role of zinc sulphate application on growth and biochemical responses - Sadaf Saeed; Awais Manzoor; Arslan Haider; Tahrim Ramzan; Hafeez ur Rehman; Muhammad Ahmad; Shahzad Bashir; Usman Zulfiqar; Muhammad Nazim; Muhammad Faisal Maqsood; Waleed A. A. Alsakkaf; Hayssam M. Ali (Environmental Science and Pollution Research, 2025)

Review of single-atom electrocatalysts for hydrogen and oxygen evolution reactions from water-splitting - Muhammad Shoaib; Muhammad Yasin Naz; Tong Wu; Hafeez Ur Rehman; Enqi Sun; Aiping Li; Qiliang Zhu; Ning Wang (Fuel, 2025)

Effects of enzyme supplementation and fermentation in canola-based diets on growth performance, intestinal viscosity and histomorphology in broiler chickens during the finisher phase - Wasim Akram; Abdul Hafeez; Sarzamin Khan; Muhammad Tahir; Rifat Ullah Khan (Tropical Animal Health and Production, 2025)

Combined Application of Plant Growth Promoting Rhizobacteria and Kinetin on Maize Growth, Chlorophyll, Osmoregulation, and Oxidative Metabolism Under Drought Stress - Rubaika Khurshid; Shagufta Perveen; Muhammad Bilal Hafeez; Abid Niaz; Saeedeh Zarbakhsh (Journal of Soil Science and Plant Nutrition, 2025)

Rhizospheric crosstalk: A mechanistic overview of how plant secondary metabolites alleviate abiotic stresses - Ali Muhammad; Muhammad Hafeez Ullah Khan; Xiangjun Kong; Shuaichao Zheng; Na Bai; Lijie Li; Nina Zhang; Sajid Muhammad; Zengqiang Li; Xiaotian Zhang; Chen Miao; Zhiyong Zhang (Plant Science, 2025)

Machine learning-driven classification of Pb Zn ore deposits using pyrite trace elements and isotopic signatures: A case study of the Gunga deposit - Muhammad Amar Gul; Huishan Zhang; Yanguang Li; Xiaoyong Yang; Chao Sun; Xiaojian Zhao; Guangli Ren; Asia Kanwal; Muhammad Hafeez; Yu Yang; Rizwan Sarwar Awan; Mohamed Faisal (Journal of Geochemical Exploration, 2025)

“Sustainable energy for all” how this undermines human development: an operational and statistical analysis - Mushtaque Ahmed Laghari; Muhammad Javeed Akhter; Hafeez ur Rehman; Qaisar Abbas (Environment, Development and Sustainability, 2025)

Taurine decreases arsenic and microplastic toxicity in broccoli (Brassica oleracea L.) through functional and microstructural alterations - Shahar Yar; Muhammad Arslan Ashraf; Rizwan Rasheed; Umer Farooq; Arslan Hafeez; Shafaqat Ali; Mudassar Shahid; Pallab K. Sarker (BioMetals, 2025)

Organic and inorganic amendments improved the morpho-physiological and nutritional status of moringa (Moringa oleifera) genotypes - Madeeha kauser; Ejaz Ahmad Waraich; Hafeez ur Rehman; Muhammad Anwar ul Haq (Acta Physiologiae Plantarum, 2025)

Corticotropin-releasing factor-like diuretic hormone 44 and five corresponding GPCRs in Drosophila suzukii: Structural and functional characterization - Hojung Yoon; Briana Price; Ryssa Parks; Hyo Sang Jang; Muhammad Hafeez; Jacob Corcoran; Seung-Joon Ahn; Man-Yeon Choi (Journal of Insect Physiology, 2025)

Geospatial assessment of climate variability and drought patterns: a case study from Pakistan - Sher Shah Hassan; Muhammad Arif Goheer; Humera Farah; Faiza Hafeez; Khurram Sheraz; Javaria Fahad; Aqil Tariq (Theoretical and Applied Climatology, 2025)

Plant Growth Promoters (PGPs) Alleviate Salt Stress, Enhance Physiological Parameters, Secondary Metabolites and Silymarin Content in Milk Thistle - Noreen Zahra; Abdul Wahid; Muhammad Bilal Hafeez; Muhammad Waqas; Abida Kausar; Abdulaziz Abdullah Alsahli (Journal of Soil Science and Plant Nutrition, 2025)

Unraveling insect feeding patterns and their ecological impacts on plant defense mechanisms - Arzlan Abbas; Muhammad Zulqar Nain Dara; Farman Ullah; Babu Saddam; Sohail Abbas; Aleena Alam; Mobeen Babar; Faisal Hafeez; Muhammad Dildar Gogi; Hamed A. Ghramh; Khalid Ali Khan; Yasir Niaz; et al. (Journal of Plant Diseases and Protection, 2025)

Investigating Bemisia tabaci (Hemiptera: Aleyrodidae) resistance mechanisms: a comprehensive analysis of variable responses to selective insecticides - Dilbar Hussain; Muhammad Saleem; Muhammad Sohail Qadir; Kanwal Hanif; Faisal Hafeez; Usama Saleem; Muhammad Jawad Saleem; Muhammad Bilal Bin Iqbal; Muhammad Zubair (International Journal of Tropical Insect Science, 2025)

Environmental innovation and human capital: an environmental regulation choice for a carbon-neutral economy - Liu Jie; Javier Cifuentes-Faura; Shikuan Zhao; Muhammad Hafeez; Ousama Ben Salha (Air Quality, Atmosphere & Health, 2025)

Climate change projections for Diamer Division in lesser Himalayas using multi-global climate model ensemble - Didar Ahmad; Faridullah Faridullah; Muhammad Irshad; Aziz Ur Rahim Bacha; Farhan Hafeez; Akhtar Iqbal; Zahid Ullah; Muhammad Naveed Afridi; Abdulwahed Fahad Alrefaei; Rashid Nazir (Environmental Science and Pollution Research, 2024)

Conservation agriculture effects on ecosystem health and sustainability – A review of rice–wheat cropping system - Muhammad Farooq; Ahmad Nawaz; Abdul Rehman; Aman Ullah; Abdul Wakeel; Hafeez ur Rehman; Ahmad Nawaz; Kadambot H.M. Siddique; Michael Frei (Science of The Total Environment, 2024)

Dyna-PINN: Physics-informed deep dyna-q reinforcement learning for intelligent control of building heating system in low-diversity training data regimes - Muhammad Hafeez Saeed; Hussain Kazmi; Geert Deconinck (Energy and Buildings, 2024)

Breeding for water-use efficiency in wheat: progress, challenges and prospects - Aqsa Hafeez; Shehzad Ali; Muhammad Ammar Javed; Rashid Iqbal; Muhammad Nauman Khan; Fatih ÇIĞ; Ayman EL Sabagh; Turki Abujamel; Steve Harakeh; Sezai Ercisli; Baber Ali (Molecular Biology Reports, 2024)

Effect of Plant Growth Regulators On Water Relations, Proximate Composition, and Ascorbate/glutathione Cycle of Late-sown Wheat Under Saline Conditions - Muhammad Bilal Hafeez; Abdul Ghaffar; Noreen Zahra; Naeem Ahmad; Ali Raza; Rui Wang; Jun Li (Journal of Crop Health, 2024)

Elucidating the protective role of manganese seed priming in mitigating lead-induced oxidative stress: enhancements in growth, grain yield, and antioxidant activities of wheat - Abida Parveen; Muhammad Atif; Faiza Akhtar; Shagufta Perveen; Sara Zafar; Khadija Hafeez; Nadia Yasmeen (Environmental Science and Pollution Research, 2024)

Towards safer mining environments: an in-depth review of predictive models for accidents - Kausar Sultan Shah; Hafeez Ur Rehman; Niaz Muhammad Shahani; Barkat Ullah; Naeem Abbas; Muhammad Junaid; Mohd Hazizan bin Mohd Hashim (Arabian Journal of Geosciences, 2024)

Income inequality-renewable energy demand nexus in emerging Asian economies: does asymmetry matter? - Yannan Gao; Danish Ahmed; Muhammad Hafeez; Qaisar Ali; Yawar Abbas; Adnan Maqbool (Environmental Science and Pollution Research, 2024)

Challenges and opportunities for the application of digital twins in hard-to-abate industries: a review - Muhammad Azam Hafeez; Alberto Procacci; Axel Coussement; Alessandro Parente (Resources, Conservation and Recycling, 2024)

Triboelectrically active and wettability-swichable magnetic textile for self-powered intelligent marine conservation - Qiliang Zhu; Tong Wu; Enqi Sun; Shuchang Meng; Zequan Zhao; Yifei Wang; Lei Zhang; Zimeng Ma; Muhammad Shoaib; Hafeez Ur Rehman; Xia Cao; Ning Wang (Chemical Engineering Journal, 2024)

Recent Advances in Plant Drought Tolerance - Muhammad Farooq; Abdul Wahid; Noreen Zahra; Muhammad Bilal Hafeez; Kadambot H. M. Siddique (Journal of Plant Growth Regulation, 2024)

Zinc solubilizing bacteria synergize the effect of zinc sulfate on growth, yield and grain zinc content of rice (Oryza sativa) - Muhammad Shakeel; Fauzia Yusuf Hafeez; Imran Riaz Malik; Abdur Rauf; Farooq Jan; Ikramullah Khan; Iram Ijaz; Mohamed Farouk Elsadek; Muhammad Ajmal Ali; Kamran Rashid; Muhammad Muzammal; Muhammad Munir; et al. (Cereal Research Communications, 2024)
Zinc solubilizing bacteria inhabiting root endosphere possesses great potential to enhance plant yield by solubilizing the nutrients. The potential of Zn solubilizing bacteria Bacillus sp. SH-10 and Bacillus cereus SH-17 to improve yield and grain zinc content of rice was investigated under different regimes of individual and co-inoculation in the presence and absence of chemical fertilizer zinc sulfate (ZnSO 4 ). The strains were applied to the rice varieties basmati 385 and super basmati under field conditions for two consecutive years. A significantly improved growth of rice plants, such as plant height (102–118 cm), number of tillers per plant (8.5–11.5), chlorophyll content (29.5–35.1), zinc requiring enzymes, i.e., superoxide dismutase (396–570 per gram fresh weight (g −1 FW)), carbonic anhydrase activity (CA) (10–15.06 U g −1 FW) and grain yield (3.0–3.8 tons ha −1 ), was observed in the plants inoculated with Bacillus sp. in the presence of chemical fertilizer (ZnSO 4 ). Consortium of zinc solubilizing bacteria also caused higher grain Zn content (25.0–30.5 mg kg −1 ) of the rice varieties basmati 385 and super basmati as compared to that of un-inoculated plants. Hence, it can be concluded that Zn solubilizing bacteria has immense potential to be used as agricultural crop inoculants as they synergize the effect of chemical Zn, increase yield and improve the nutritional value of crops.

Exploring the efficacy of plant growth promoters in nutrient acquisition and antioxidant defense responses of late sown wheat under saline conditions - Muhammad Bilal Hafeez; Abdul Ghaffar; Noreen Zahra; Naeem Ahmad; Wahidah H. Al-Qahtani; Pankaj Sharma; Azamal Husen; Jun Li (South African Journal of Botany, 2024)

Molecular insights into the functional analysis of P450 CYP321A7 gene in the involvement of detoxification of lambda-cyhalothrin in Spodoptera frugiperda - Wan-Ting Li; Jia-Yu Lin; Jia-Jie Liu; Muhammad Hafeez; Shi-Wen Deng; Hong-Yu Chen; Rong-Jie Ren; Muhammad Shoaib Rana; Rui-Long Wang (Pesticide Biochemistry and Physiology, 2024)

Retraction Note: Nexus between energy policy and environmental performance in China: The moderating role of green finance adopted firms - Muhammad Ghazanfar Abbas; Zhuquan Wang; Shahid Bashir; Wasim Iqbal; Hafeez Ullah (Environmental Science and Pollution Research, 2024)

Impact of cement waste on soil fertility and crop productivity: a serious concern for food security - Junaid Iqbal; Muhammad Jamal Khan; Muhammad Hafeez; Junaid Ali Siddiqui; Muhammad Fahad; Bahar Ali; Muhammad Imran; Aqeel Ahmad; Shah Fahad (Environmental Science and Pollution Research, 2024)

From perception to prediction: A comparative study of thermal comfort assessment techniques in school facilities - Tajudeen Dele Mustapha; Ahmad Sanusi Hassan; Muhammad Hafeez Abdul Nasir; Fatemeh Khozaei; Yasser Arab (Energy and Buildings, 2024)

Bio-formulated chitosan nanoparticles enhance disease resistance against rice blast by physiomorphic, transcriptional, and microbiome modulation of rice (Oryza sativa L.) - Rahila Hafeez; Junning Guo; Temoor Ahmed; Hubiao Jiang; Mubashar Raza; Muhammad Shahid; Ezzeldin Ibrahim; Yanli Wang; Jiaoyu Wang; Chengqi Yan; Qianli An; Jason C. White; et al. (Carbohydrate Polymers, 2024)

Exploring the phytochemical, antioxidant, antimicrobial and analgesic potentials of Solanum erianthum as an alternative biological feedstock for producing sustainable biochemicals - Muhammad Ajaib; Sairah Hafeez Kamran; Muhammad Faheem Siddiqui; Muhammad Qasim; Muhammad Azeem; Zainul Abideen; Attiat Elnaggar; Ali El-Keblawy (Biocatalysis and Agricultural Biotechnology, 2024)

Long-Term Follow-Up of Cerebral Aneurysms Completely Occluded at 6 Months After Intervention with the Woven EndoBridge (WEB) Device: a Retrospective Multicenter Observational Study - Kareem El Naamani; Panagiotis Mastorakos; Nimer Adeeb; Mathews Lan; James Castiglione; Omaditya Khanna; Jose Danilo Bengzon Diestro; Rachel M. McLellan; Mahmoud Dibas; Justin E. Vranic; Assala Aslan; Hugo H. Cuellar-Saenz; et al. (Translational Stroke Research, 2024)

Correction: Taurine Enervates Nickel Stress in Lagenaria siceraria by Regulating Redox Balance, Methylglyoxal Detoxification, H2S Production, and Nickel Uptake - Arslan Hafeez; Rizwan Rasheed; Muhammad Rizwan; Noman Habib; Sadia Zafar; Mudassir Iqbal Shad; Shafaqat Ali; Muhammad Arslan Ashraf (Journal of Soil Science and Plant Nutrition, 2024)

Taurine Enervates Nickel Stress in Lagenaria siceraria by regulating Redox Balance, Methylglyoxal Detoxification, H2S Production, and Nickel Uptake - Arslan Hafeez; Rizwan Rasheed; Muhammad Rizwan; Noman Habib; Sadia Zafar; Mudassir Iqbal Shad; Shafaqat Ali; Muhammad Arslan Ashraf (Journal of Soil Science and Plant Nutrition, 2024)

Insect resilience: unraveling responses and adaptations to cold temperatures - Farman Ullah; Arzlan Abbas; Hina Gul; Ali Güncan; Muhammad Hafeez; Basana-Gowda Gadratagi; Lizette Cicero; Ricardo Ramirez-Romero; Nicolas Desneux; Zhihong Li (Journal of Pest Science, 2024)

Exogenous Application of Plant Growth Regulators Improves Economic Returns, Grain Yield and Quality Attributes of Late-Sown Wheat under Saline Conditions - Muhammad Bilal Hafeez; Abdul Ghaffar; Noreen Zahra; Naeem Ahmad; Hira Shair; Muhammad Farooq; Jun Li (International Journal of Plant Production, 2024)

Unraveling the contribution of copper seed priming in enhancing chromium tolerance in wheat by improving germination, growth, and grain yield - Khadija Hafeez; Muhammad Atif; Shagufta Perveen; Abida Parveen; Faiza Akhtar; Nadia Yasmeen (Environmental Science and Pollution Research, 2024)

Application of Synthetic Iron Oxyhydroxide with Influencing Factors for Removal of As(V) and As(III) from Groundwater - Shakeel Ahmed Talpur; Muhammad Yousuf Jat Baloch; Chunli Su; Javed Iqbal; Aziz Ahmed; Hafeez Ahmed Talpur (Journal of Earth Science, 2024)

Pervasive influence of heavy metals on metabolic pathways is potentially relieved by hesperidin to enhance the phytoremediation efficiency of Bassia scoparia - Mazhar Hussain; Arslan Hafeez; Muhammad Rizwan; Rizwan Rasheed; Mahmoud F. Seleiman; Muhammad Arslan Ashraf; Shafaqat Ali; Umer Farooq; Muhammad Nafees (Environmental Science and Pollution Research, 2024)

Integrative transcriptomic and metabolomic analyses reveals the toxicity and mechanistic insights of bioformulated chitosan nanoparticles against Magnaporthe oryzae - Rahila Hafeez; Junning Guo; Temoor Ahmed; Ezzeldin Ibrahim; Md. Arshad Ali; Muhammad Rizwan; Munazza Ijaz; Qianli An; Yanli Wang; Jiaoyu Wang; Bin Li (Chemosphere, 2024)

Effect of different concentrations of resveratrol on nuclear maturation and in-vitro development competence of oocytes of Nili Ravi buffalo - Samar Wafa Kabeer; Amjad Riaz; Aziz Ul-Rahman; Rana Muhammad Shahbakht; Ahsan Anjum; Hafeez ur Rehman Ali Khera; Ali Haider; Faisal Riaz; Riffat Yasin; Muhammad Yaseen; Muhammad Saleem; Naheed Bano; et al. (Tropical Animal Health and Production, 2024)

Ameliorative effects of Atriplex crassifolia (C.A.Mey) on pain and inflammation through modulation of inflammatory biomarkers and GC–MS-based metabolite profiling - Sarah Rehman; Saiqa Ishtiaq; Muhammad Khalil-Ur-Rehman; Sairah Hafeez Kamran (Inflammopharmacology, 2024)

Soil Carbon Mineralization and Aggregate Distribution in Various Tillage Practices of Rice–Wheat Cropping System: A Field and Laboratory Study - Naeem Ahmad; Ahmad Latif Virk; Muhammad Bilal Hafeez; Zheng-Rong Kan; Zujiao Shi; Rui Wang; Hafiz Muhammad Waleed Iqbal; Muhammad Ishaq Asif Rehmani; Xiaoli Wang; Rattan Lal; Jun Li (Journal of Soil Science and Plant Nutrition, 2024)

Seed nutripriming with magnesium to improve seedling growth and yield in wheat: Consequences for seed nutrient reserves metabolism and photochemical efficiency - Muhammad Irfan; Mashael M. Alotibib; Nahaa M. Alotaibi; Adel M. Ghoneim; Hafeez ur Rehman; Farahat S. Moghanm (South African Journal of Botany, 2024)

Risk surveillance with spatial distribution of Organochlorine Pesticides (OCPs) from sedimentary samples of Chenab River - Sidra Siddique; M. Nawaz Chaudhry; Sajid Rashid Ahmad; Rabia Nazir; Rimsha Javed; Muhammad Rashid Hafeez; Yasser Alraey; Lalita Ambigai Sivasamugham; Adeel Mahmood (Science of The Total Environment, 2024)

The application of entomopathogenic nematode modified microbial communities within nesting mounds of the red imported fire ants, Solenopsis invicta - Xiaowei Li; Songwang Yi; Limin Chen; Muhammad Hafeez; Zhijun Zhang; Jinming Zhang; Shuxing Zhou; Wanying Dong; Jun Huang; Yaobin Lu (Science of The Total Environment, 2024)

Mineral resource volatility and green growth: The role of technological development, environmental policy stringency, and trade openness - Meihong Feng; Donghang Zou; Muhammad Hafeez (Resources Policy, 2024)

Carbon trade-off and energy budgeting under conventional and conservation tillage in a rice-wheat double cropping system - Naeem Ahmad; Ahmad Latif Virk; Abdul-Sattar Nizami; Rattan Lal; Scott X. Chang; Muhammad Bilal Hafeez; Xingyu Guo; Rui Wang; Xiaoli Wang; Hafiz Muhammad Waleed Iqbal; Gadah Albasher; Jun Li (Journal of Environmental Management, 2024)

Evaluating the Morpho-physiological Responses of Stevia (Stevia rebaudiana) to Foliar Application of Various Plant Growth Promoters Under Drought Stress - Fatima Ahmadzai; Kanval Shaukat; Hafiz Mohammad Akram; Mahmood ur Rehman Ansari; Noreen Zahra; Abdul Samad; Mereen Nizar; Muhammad Bilal Hafeez; Ali Raza (Journal of Crop Health, 2024)

Three-dimensional hydrodynamic modelling of saltwater ingression and circulation in a Brackish Lake Shinji, Japan - Muhammad Ali Hafeez; Tetsunori Inoue (Advances in Water Resources, 2024)

How do mineral resources trade and financial development affect green entrepreneurship in resource-rich economies? - Ping Chen; JunYa Xi; Yuming Li; Ilhan Ozturk; Sana Ullah; Muhammad Hafeez (Resources Policy, 2024)

Effective biological control of Lentil (Lens culinaris) Fusarium wilt and plant growth promotion through native Rhizobacteria - Javeria Ayub; Ayesha Tahir; Umer Iqbal; Huma Ayub; Muhammad Zeeshan Hyder; Amna Kiyani; Fauzia Yusuf Hafeez; Muhammad Kashif Ilyas; Abdul Ghafoor; Tayyaba Yasmin (Physiological and Molecular Plant Pathology, 2024)

Comparative taxonomy and evolutionary significance of foliar epidermis in Jasminum L. (Oleaceae) based on light and scanning electron microscopy - Naeem Akhtar; Muhammad Q. Hayat; Umer Habib; Muhammad A. Khan; Saad I. Malik; Hina Hafeez; Adil Hussain; Azhar Hussain; Daniel Potter (Flora, 2024)

Quantifying future water-saving potential under climate change and groundwater recharge scenarios in Lower Chenab Canal, Indus River Basin - Muhammad Shafeeque; Mohsin Hafeez; Abid Sarwar; Arfan Arshad; Tahira Khurshid; Muhammad Irfan Asim; Shoaib Ali; Adil Dilawar (Theoretical and Applied Climatology, 2024)
Quantifying water-saving potential (WSP) is crucial for sustainable water resource management in canal command areas and river basins. Previous studies have partially or fully ignored the importance of groundwater in WSP assessments, particularly in irrigated areas. This study is aimed at quantifying WSP in the Lower Chenab Canal (LCC) command area of the Indus River Basin, Pakistan, under various scenarios of future climate change and groundwater recharge. These quantifications are conducted using an empirical model based on the Budyko theory. The model was forced using observed, remote sensing, and CMIP6 future climate data for two Shared Socioeconomic Pathways (SSP245 and SSP585) and their ensembles (cold-dry, cold-wet, warm-dry, and warm-wet) for possible futures. The results showed that the average WSP in the LCC command area was 466 ± 48 mm/year during the historical period (2001–2020). The WSP is projected to decrease by – 68 ± 3% under the warm-dry ensemble scenario (SSP245 and SSP585) and – 48 ± 13% under the ensembled cold-wet scenario by 2100. The results also demonstrated that WSP could be increased by up to 70 ± 9% by artificially recharging 20% of the abstracted groundwater per year in the LCC command area by the late twenty-first century. Our findings highlight the importance of adopting artificial groundwater recharge to enhance the WSP and sustainably manage water resources in the LCC command area. Policymakers should consider these findings when deciding on water resource management in the Indus River Basin.

Effects of incorporating pine-woodchip biochar with reduced NP fertilizer on calcareous soil characteristics, organic carbon, NPK availability, and maize productivity - Waqas Ali Akbar; Hafeez Ur Rahim; Muhammad Irfan; Juha M. Alatalo; Muhammad Mudasssir; Jochen Bundschuh (Journal of Soils and Sediments, 2024)

Deciphering the Role of Phytohormones and Osmolytes in Plant Tolerance Against Salt Stress: Implications, Possible Cross-Talk, and Prospects - Sadam Hussain; Muhammad Bilal Hafeez; Rabia Azam; Kashf Mehmood; Marjan Aziz; Sezai Ercisli; Talha Javed; Ali Raza; Noreen Zahra; Saddam Hussain; Xiaolong Ren (Journal of Plant Growth Regulation, 2024)

Assessment of heavy metal distribution and bioaccumulation in soil and plants near coal mining areas: implications for environmental pollution and health risks - Waqas Ali Akbar; Hafeez Ur Rahim; Muhammad Irfan; Adiba Khan Sehrish; Muhammad Mudassir (Environmental Monitoring and Assessment, 2024)

Marine plastic pollution detection and identification by using remote sensing-meta analysis - Muhammad Waqas; Man Sing Wong; Alessandro Stocchino; Sawaid Abbas; Sidrah Hafeez; Rui Zhu (Marine Pollution Bulletin, 2023)

An assessment of resource curse hypothesis for Chinese economy - Bing Cao; li Biqing; Jiaying li; Muhammad Hafeez (Resources Policy, 2023)

Assessing the COVID-19 impact on economy, health and natural resource prices: An evidence from selected Asian economies - ShiYong Zheng; Xiao Li; Juan Li; Biqing Li; Muhammad Hafeez (Resources Policy, 2023)

Developing energy flexibility in clusters of buildings: A critical analysis of barriers from planning to operation - Jérôme Le Dréau; Rui Amaral Lopes; Sarah O'Connell; Donal Finn; Maomao Hu; Humberto Queiroz; Dani Alexander; Andrew Satchwell; Doris Österreicher; Ben Polly; Alessia Arteconi; Flavia de Andrade Pereira; et al. (Energy and Buildings, 2023)

Correction to: The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

Role of Aminolevulinic Acid in Mediating Salinity Stress Tolerance in Sunflower (Helianthus annuus L.) - Irfana Lalarukh; Noreen Zahra; Aleena Shahzadi; Muhammad Bilal Hafeez; Sehar Shaheen; Abida Kausar; Ali Raza (Journal of Soil Science and Plant Nutrition, 2023)

Exploring the moderating effect of globalization, financial development and environmental degradation nexus: a roadmap to sustainable development - Tayyaba Rani; Muhammad Asif Amjad; Nabila Asghar; Hafeez Ur Rehman (Environment, Development and Sustainability, 2023)

Does environmental policy stringency influence CO2 emissions in the Asia Pacific region? A nonlinear perspective - Linlin Liu; Liwei Pang; Hong Wu; Muhammad Hafeez; Raufhon Salahodjaev (Air Quality, Atmosphere & Health, 2023)

Utilisation of Sunflower Marble Waste Nanocomposites for Efficient Removal of Dyes from Wastewater: Synthesis, Adsorption Performance, and Characterisation - Tayaba Saeed; Muhammad Asif Hanif; Umer Rashid; Hafeez Anwar; Ijaz Ahmad Bhatti; Fahad A. Alharthi; Jeehoon Han; Jiyun Yoo (Water, Air, & Soil Pollution, 2023)

Plant breeding for harmony between sustainable agriculture, the environment, and global food security: an era of genomics‐assisted breeding - Aqsa Hafeez; Baber Ali; Muhammad Ammar Javed; Aroona Saleem; Mahreen Fatima; Amin Fathi; Muhammad Siddique Afridi; Veysel Aydin; Mükerrem Atalay Oral; Fathia A. Soudy (Planta, 2023)

Nanotechnologies for environmental remediation and their ecotoxicological impacts - Mahnoor Ejaz; Alvina Gul; Munir Ozturk; Ahmed Hafeez; Bengu Turkyilmaz Unal; Sami Ullah Jan; Muhammad Taimur Siddique (Environmental Monitoring and Assessment, 2023)

Unraveling the impact of human perturbation on nitrogen cycling in terrestrial ecosystems of lower Himalaya, Pakistan - Tahir Zaman; Saeed Ahmad Asad; Muhammad Irshad; Faridullah; Muhammad Shahzad; Rashid Nazir; Awais Arefeen; Akhtar Iqbal; Farhan Hafeez (Environmental Monitoring and Assessment, 2023)

Emerging trends in insect sex pheromones and traps for sustainable management of key agricultural pests in Asia: beyond insecticides—a comprehensive review - Aleena Alam; Sohail Abbas; Arzlan Abbas; Muneer Abbas; Faisal Hafeez; Muhammad Shakeel; Feng Xiao; Chen Ri Zhao (International Journal of Tropical Insect Science, 2023)

Lithospheric velocity structure of South China Sea basin from ocean bottom seismometer ambient noise tomography - Liqun Cheng; Yinxia Fang; Xiongwei Niu; Tingzi Li; Chongzhi Dong; Yanghui Zhao; Hao Hu; Fansheng Kong; Pingchuan Tan; Aiguo Ruan; Shaoping Lu; Jianke Fan; et al. (Tectonophysics, 2023)

A systematic review of physiological signals based driver drowsiness detection systems - Adil Ali Saleem; Hafeez Ur Rehman Siddiqui; Muhammad Amjad Raza; Furqan Rustam; Sandra Dudley; Imran Ashraf (Cognitive Neurodynamics, 2023)

Adsorptive and photocatalytic degradation potential of porous polymeric materials for removal of pesticides, pharmaceuticals, and dyes-based emerging contaminants from water - Azeem Intisar; Arooj Ramzan; Shahzar Hafeez; Nazim Hussain; Muhammad Irfan; Nasir Shakeel; Komal Aziz Gill; Amjad Iqbal; Marcin Janczarek; Teofil Jesionowski (Chemosphere, 2023)

Influence of abiotic stresses on disease infestation in plants - Noreen Zahra; Muhammad Bilal Hafeez; Manal Al Shukaily; Abdullah M. Al-Sadi; Kadambot H.M. Siddique; Muhammad Farooq (Physiological and Molecular Plant Pathology, 2023)

"The promissory note at COP-21 of sustainable energy for all" Is it converging toward economic development? - Muhammad Javeed Akhtar; Hafeez Ur Rehman; Qaisar Abbas (Environment, Development and Sustainability, 2023)

Testing the resource curse hypothesis: The dynamic roles of institutional quality, inflation and growth for Dragon - ShiYong Zheng; Hua Liu; Muhammad Hafeez; Xiaofeng Wang; Shah Fahad; Xiao-Guang Yue (Resources Policy, 2023)

The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

Single Pot Enzymatic Treatment of Sugarcane Bagasse Using Laccase and Cellulase for the Production of Value-Added Products - Usama Hafeez; Muhammad Sohail; Syed Tariq Ali (Sugar Tech, 2023)

Effect of exogenous taurine on growth, oxidative defense, and nickel (Ni) uptake in canola (Brassica napus L.) under Ni stress - Muhammad Arslan Ashraf; Arslan Hafeez; Rizwan Rasheed; Iqbal Hussain; Umer Farooq; Muhammad Rizwan; Shafaqat Ali (Physiology and Molecular Biology of Plants, 2023)

Improved photocatalytic decolorization of reactive black 5 dye through synthesis of graphene quantum dots–nitrogen-doped TiO2 - Muhammad Saqib Khan; Nadia Riaz; Saeed Rehman; Liu Chenhui; Ahson Jabbar Shaikh; Muhammad Arfan; Iftikhar Zeb; Muhammad Arshad; Farhan Hafeez; Muhammad Bilal (Environmental Science and Pollution Research, 2023)

Influence of heat stress during grain development on the wheat grain yield, quality, and composition - Muhammad Bilal Hafeez; Noreen Zahra; Abida Kausar; Jun Li; Abdul Rehman; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2023)

Modulation of growth and biochemical responses in spinach (Spinacia oleracea L.) through foliar application of some amino acids under drought conditions - Abida Kausar; Noreen Zahra; Hira Tahir; Muhammad Bilal Hafeez; Waseem Abbas; Ali Raza (South African Journal of Botany, 2023)

Evaluation of Physio-Morphological and Biochemical Responses for Salt Tolerance in Wheat (Triticum aestivum L.) Cultivars - Muhammad Arslan Ashraf; Arslan Hafeez; Rizwan Rasheed; Iqbal Hussain; Umer Farooq; Muhammad Rizwan; Shafaqat Ali (Journal of Plant Growth Regulation, 2023)

Observing the response of environmental and economic performances to tourism in light of structural changes - Muhammad Wasim Akram; Shuchun Yang; Muhammad Hafeez (Air Quality, Atmosphere & Health, 2023)

Fiscal policy-green growth nexus: Does financial efficiency matter in top carbon emitter economies? - Huizheng Liu; Muhammad Afaq Haider Jafri; Peihua Zhu; Muhammad Hafeez (Environment, Development and Sustainability, 2023)

Sublethal effects of spinetoram and emamectin benzoate on key demographic parameters of fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae) under laboratory conditions - Arzlan Abbas; Chen Ri Zhao; Muhammad Arshad; Xiao Han; Ayesha Iftikhar; Faisal Hafeez; Asad Aslam; Farman Ullah (Environmental Science and Pollution Research, 2023)

Green growth and carbon neutrality targets in China: Do financial integration and ICT matter? - ShiYong Zheng; Danish Ahmed; Yuantao Xie; Muhammad Tariq Majeed; Muhammad Hafeez (Journal of Cleaner Production, 2023)

Evaluation of haematological, serum biochemical and oxidative stress parameters in cattle naturally infected with lumpy skin disease virus - Aziz Ul-Rahman; Muhammad Furqan Shahid; Muhammad Zahid Iqbal; Aijaz Ali Channa; Majeeda Rasheed; Muhammad Adnan; Rauf Mahmood; Hafiz Muhammad Ishaq; Hafeez ur Rehman Ali Khera; Kashif Hussain; Muhammad Asif Raza (Tropical Animal Health and Production, 2023)

Potassium-Nitrogen Ratio Improved Cotton Yield by Regulating Antioxidant Metabolism Under a New Cropping Model for the Yangtze River Valley of China - Saif Ali; Abdul Hafeez; Xiaolei Ma; Shahbaz Atta Tung; Muhammad Sohaib Chattha; Shoaib Ahmad; Adnan Noor Shah; Guozheng Yang (Journal of Soil Science and Plant Nutrition, 2023)

Nitrogen Management Strategies to Improve Crop Performance, Recovery Efficiency and Their Relationship with Physiological Indices in Dry Direct-Seeded Rice - Hafeez ur Rehman; Imran Ali; Fiaz Ali; Masood Iqbal Awan; Abdul Wakeel; Muhammad Farooq; Mubshar Hussain (International Journal of Plant Production, 2023)

Natural resources, fiscal decentralization, and environmental quality in China: an empirical analysis from QARDL approach - Mei Zhang; Muhammad Hafeez; Chaudhry Muhammad Nadeem Faisal; Muhammad Shahzad Iqbal (Environmental Science and Pollution Research, 2023)

Adaptation of coastal defence structure as a mechanism to alleviate coastal erosion in monsoon dominated coast of Peninsular Malaysia - Wan Shiao Dong; Effi Helmy Ariffin; Cherdvong Saengsupavanich; Muhammad Aizat Mohd Rashid; Mohamad Hakim Mohd Shukri; Muhammad Zahir Ramli; Mohd Fuad Miskon; Muhammad Hafeez Jeofry; Kamaruzzaman Yunus; Nor Hisham M. Ghazali; Md Nasir Md Noh (Journal of Environmental Management, 2023)

Eco-innovation and environmental entrepreneurship: steps towards business growth - Muhammad Wasim Akram; Shuchun Yang; Muhammad Hafeez; Md. Abdul Kaium; Israt Zahan; Raufhon Salahodjaev (Environmental Science and Pollution Research, 2023)

Asian logistics industry efficiency under low carbon environment: policy implications for sustainable development - Muhammad Wasim Akram; Muhammad Hafeez; Shuchun Yang; Narayan Sethi; Shaza Mahar; Raufhon Salahodjaev (Environmental Science and Pollution Research, 2023)

Erratum to ‘Role of endophytic bacteria in salinity stress amelioration by physiological and molecular mechanisms of defense: A comprehensive review’ South African Journal of Botany, Volume 151, December 2022, Pages 33-46 - Baber Ali; Aqsa Hafeez; Muhammad Ammar Javed; Muhammad Siddique Afridi; Hina Ali Abbasi; Ayesha Qayyum; Tayyaba Batool; Abid Ullah; Romina Alina Marc; Soad K. Al Jaouni; Dalal Hussien M. Alkhalifah; Samy Selim (South African Journal of Botany, 2023)

Effect of environmental taxes on environmental innovation and carbon intensity in China: an empirical investigation - Qian Zhang; Saba Anwer; Muhammad Hafeez; Atif Khan Jadoon; Zahoor Ahmed (Environmental Science and Pollution Research, 2023)

Southern South China Sea Dynamics: Sea Level Change from Coupled Model Intercomparison Project Phase 6 (CMIP6) in the 21st Century - Noah Irfan Azran; Hafeez Jeofry; Jing Xiang Chung; Liew Juneng; Syamir Alihan Showkat Ali; Alex Griffiths; Muhammad Zahir Ramli; Effi Helmy Ariffin; Mohd Fuad Miskon; Juliana Mohamed; Kamaruzzaman Yunus; Mohd Fadzil Akhir (Journal of Marine Science and Engineering, 2023)
Sea level rise will significantly impact coastal areas around the world. As a coastal country, Malaysia’s rising sea levels are a significant concern because they would affect 70% of its population. The study of sea level rise is important in order to implement effective mitigation and adaptation strategies. This study investigates the performance of CMIP6 Global Climate Models (GCMs) in simulating sea level rise in the Malaysian seas using various statistical methods. The models’ performances were evaluated by comparing historic CMIP6 GCM runs from 1993 to 2010 with sea level measurements from the satellite altimetry AVISO+ using the Taylor diagram. The SCS (SCSPM and SCSEM) had a higher sea level range and trend in both selected areas than the SM and SS. With 1.5 °C warmings, the multi-model ensemble means predicted that the SCS would rise by 16 mm near the Peninsular, with sea levels increasing by 0.908 m at a rate of 1.5 mm/year, and by 14.5 mm near East Malaysia, with sea levels increasing by 0.895 m at a rate of 1.1 mm/year. In contrast, 2.0 °C warmings project that SCSPM and SCSEM would cause sea levels to rise by 20.2 mm and 21.5 mm, respectively, at a rate of 0.6 mm/year and 0.7 mm/year. This information will provide an insight into Malaysian sea levels between now and the end of the twenty-first century, which will be beneficial for government agencies, academics, and relevant stakeholders.

An approach to the pollution haven and pollution halo hypotheses in Asian countries - Muhammad Ali Abbasi; Misbah Nosheen; Hafeez Ur Rahman (Environmental Science and Pollution Research, 2023)

Small organic molecules as fluorescent sensors for the detection of highly toxic heavy metal cations in portable water - Ramsha Iftikhar; Iqra Parveen; Ayesha; Aqsa Mazhar; Muhammad Saqlain Iqbal; Ghulam Mustafa Kamal; Freeha Hafeez; Ai Ling Pang; Mohsen Ahmadipour (Journal of Environmental Chemical Engineering, 2023)

Optimization of carboxylated graphene oxide (C-GO) content in polymer matrix: Synthesis, characterization, and application study - Zulfiqar Ahmad Rehan; Muhammad Zahid; Sidra Kanwal; Nimra Nadeem; Asif Hafeez; Asif Jamil; Zakariya Zubair (Chemosphere, 2023)

Hydrogen Production through Water Vapors using Optimized Corona-DBD Hybrid Plasma Micro-Reactor - Muhammad Younas; Sumeer Shafique; Abrar Faisal; Ainy Hafeez; Fahed Javed; Maria Mustafa; Fahad Rehman (Fuel, 2023)

How do financial fragility and ICT penetration affect renewable energy consumption and green growth in top-polluting economies? - Muhammad Wasim Akram; Danish Ahmed; Anna Trunina; Kashif Hamid; Muhammad Hafeez (Environmental Science and Pollution Research, 2022)

Do transportation taxes promote pro-environmental behaviour? An empirical investigation - Lei Wang; Ziwang Chen; Muhammad Tariq Mahmood; Mirza Nasir Jahan Mehdi; Sana Ullah; Muhammad Nazam; Muhammad Hafeez (Environmental Science and Pollution Research, 2022)

How do energy prices and climate shocks affect human health? Insights from BRICS - Wenxin Wang; Muhammad Hafeez; Hong Jiang; Muhammad Usman Ashraf; Muhammad Asif; Muhammad Wasim Akram (Environmental Science and Pollution Research, 2022)

Plant Growth Promoters Alleviate Oxidative Damages and Improve the Growth of Milk Thistle (Silybum marianum L.) Under Salinity Stress - Noreen Zahra; Abdul Wahid; Muhammad Bilal Hafeez; Kanval Shaukat; Sobia Shahzad; Tariq Shah; Mohammed Nasser Alyemeni (Journal of Plant Growth Regulation, 2022)

Moderation of competitiveness in determining environmental sustainability: economic growth and transport sector carbon emissions in global perspective - Muhammad Shahzad Sardar; Nabila Asghar; Hafeez ur Rehman (Environment, Development and Sustainability, 2022)

Analyzing the impact of access to electricity and biomass energy consumption on infant mortality rate: a global perspective - Nabila Asghar; Muhammad Asif Amjad; Hafeez ur Rehman (Environmental Science and Pollution Research, 2022)

Revisiting the environmental impact of financial development on economic growth and carbon emissions: evidence from South Asian economies - Tayyaba Rani; Muhammad Asif Amjad; Nabila Asghar; Hafeez Ur Rehman (Clean Technologies and Environmental Policy, 2022)

Environmental factors and its influence on human health in BRICS: implications for human development - Wenxin Wang; Muhammad Hafeez; Hong Jiang; Waseem Ahmad; Hammad Badar; Raufhon Salahodjaev (Environmental Science and Pollution Research, 2022)

Green growth and environmental quality in top polluted economies: the evolving role of financial institutions and markets - Xiaomeng Deng; Juan Yang; Zahoor Ahmed; Muhammad Hafeez; Sultan Salem (Environmental Science and Pollution Research, 2022)

Do environmental technology and banking sector development matter for green growth? Evidence from top-polluted economies - Manzoor Ahmed; Muhammad Hafeez; Muhammad Abdul Kaium; Sana Ullah; Haseeb Ahmad (Environmental Science and Pollution Research, 2022)

Asymmetric macroeconomic determinants of renewable energy consumption: do financial institutions and ICT trade matter? - Lei Wang; Yingliang Huang; Abdul Ghafoor; Muhammad Hafeez; Raufhon Salahodjaev (Environmental Science and Pollution Research, 2022)

Exploring the asymmetric determinants of consumption and production-based CO2 emissions in China - Muhammad Hafeez; Juan Yang; Atif Khan Jadoon; Israt Zahan; Raufhon Salahodjaev (Environmental Science and Pollution Research, 2022)

Transportation moderation in agricultural sector sustainability — a robust global perspective - Muhammad Shahzad Sardar; Hafeez ur Rehman (Environmental Science and Pollution Research, 2022)

Comparative low lethal effects of three insecticides on demographical traits and enzyme activity of the Spodoptera exigua (Hübner) - Muhammad Hafeez; Farman Ullah; Muhammad Musa Khan; Zhangqian Wang; Hina Gul; Xiaowei Li; Jun Huang; Junaid Ali Siddiqui; Muhammad Qasim; Rui-Long Wang; Muhammad Imran; Mohammed A. Assiri; et al. (Environmental Science and Pollution Research, 2022)

Financial inclusion and its influence on economic-environmental performance: demand and supply perspectives - Dong Liu; Yuying Zhang; Muhammad Hafeez; Sana Ullah (Environmental Science and Pollution Research, 2022)

Integrated application of plant bioregulator and micronutrients improves crop physiology, productivity and grain biofortification of delayed sown wheat - Naeem Ahmad; Ahmad Latif Virk; Sadam Hussain; Muhammad Bilal Hafeez; Fasih Ullah Haider; Muhammad Ishaq Asif Rehmani; Tauqeer Ahmad Yasir; Ariba Asif (Environmental Science and Pollution Research, 2022)

Agriculture, forestry, and environmental sustainability: the role of institutions - Rizwana Yasmeen; Ihtsham Ul Haq Padda; Xing Yao; Wasi Ul Hassan Shah; Muhammad Hafeez (Environment, Development and Sustainability, 2022)

Temporal variation in leachate composition of a newly constructed landfill site in Lahore in context to environmental pollution and risks - Mahsoon Ashraf; Muhammad Zeshan; Sadia Hafeez; Rahib Hussain; Abdul Qadir; Muzaffar Majid; Farman Ahmad; Sajid Rashid Ahmad (Environmental Science and Pollution Research, 2022)

Habitat characterization of Aedes albopictus - Faisal Hafeez; Unsar Naeem-Ullah; Waseem Akram; Muhammad Arshad; Ayesha Iftikhar; Afifa Naeem; Muhammad Jawad Saleem (International Journal of Tropical Insect Science, 2022)

Susceptibility of Helicoverpa armigera Hübner (Lepidoptera: Noctuidae) on detached plant parts of transgenic and non-transgenic cotton - Muhammad Jawad Saleem; Faisal Hafeez; Qurban Ali; Asad Aslam; Muhammad Arshad; Dilbar Hussain; Ayesha Iftikhar; Afifa Naeem; Muhammad Saleem (International Journal of Tropical Insect Science, 2022)

The trade-off between economic performance and environmental quality: does financial inclusion matter for emerging Asian economies? - Dong Liu; Yuantao Xie; Muhammad Hafeez; Ahmed Usman (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Do entrepreneurial orientation and intellectual capital influence SMEs’ growth? Evidence from Pakistan - Muhammad Ghazanfar Abbas; Zhuquan Wang; Hafeez Ullah; Muhammad Mohsin; Hasnain Abbas; Memon Rafait Mahmood (Environmental Science and Pollution Research, 2022)

Identification of the soybean small auxin upregulated RNA (SAUR) gene family and specific haplotype for drought tolerance - Guang Li; Quan Wang; Lei Lu; Shoudong Wang; Xiao Chen; Muhammad Hafeez U. Khan; Yaohua Zhang; Suxin Yang (Biologia, 2022)

Assessing the dynamic linkage between energy efficiency, renewable energy consumption, and CO2 emissions in China - Wang Lei; Yuantao Xie; Muhammad Hafeez; Sana Ullah (Environmental Science and Pollution Research, 2022)

Mining public opinion: a sentiment based forecasting for democratic elections of Pakistan - Asif Nawaz; Tariq Ali; Yaser Hafeez; Saif ur Rehman; Muhammad Rizwan Rashid (Spatial Information Research, 2022)

Insect pests of economic importance attacking wheat crop (Triticum aestivum L.) in Punjab, Pakistan - Dilbar Hussain; Muhammad Asrar; Bushra Khalid; Faisal Hafeez; Muhammad Saleem; Muazzma Akhter; Maqsood Ahmed; Imran Ali; Kanwal Hanif (International Journal of Tropical Insect Science, 2022)

Does ICT diffusion lead to energy efficiency and environmental sustainability in emerging Asian economies? - Shufang Zhao; Muhammad Hafeez; Chaudhry Muhammad Nadeem Faisal (Environmental Science and Pollution Research, 2022)

Metabolic-based insecticide resistance mechanism and ecofriendly approaches for controlling of beet armyworm Spodoptera exigua: a review - Muhammad Hafeez; Farman Ullah; Muhammad Musa Khan; Xiaowei Li; Zhijun Zhang; Sakhawat Shah; Muhammad Imran; Mohammed A. Assiri; G. Mandela Fernández-Grandon; Nicolas Desneux; Muzammal Rehman; Shah Fahad; et al. (Environmental Science and Pollution Research, 2022)

Do economic policy uncertainty and financial development influence the renewable energy consumption levels in China? - Wang Lei; Lihan Liu; Muhammad Hafeez; Sidra Sohail (Environmental Science and Pollution Research, 2022)

Multidimensional perspective of green financial innovation between green intellectual capital on sustainable business: the case of Pakistan - Hafeez Ullah; Zhuquan Wang; Muhammad Mohsin; Weiying Jiang; Hasnain Abbas (Environmental Science and Pollution Research, 2022)

Assessment of sustainability and uncertainties of oil markets: mediating determinants of energy use and CO2 emissions - Muhammad Mohsin; Shahid Bashir; Zulfiqar Ali Baloch; Mohammad Hafeez (Environmental Science and Pollution Research, 2022)

Lethal and sublethal effects of emamectin benzoate on life-table and physiological parameters of citrus red mite, Panonychus citri - Muhammad Musa Khan; Muhammad Waqar Ali; Muhammad Hafeez; Ze-Yun Fan; Shaukat Ali; Bao-Li Qiu (Experimental and Applied Acarology, 2021)

RETRACTED ARTICLE: Nexus between energy policy and environmental performance in China: The moderating role of green finance adopted firms - Muhammad Ghazanfar Abbas; Zhuquan Wang; Shahid Bashir; Wasim Iqbal; Hafeez Ullah (Environmental Science and Pollution Research, 2021)

Impact of invasive ant species on native fauna across similar habitats under global environmental changes - Junaid Ali Siddiqui; Bamisope Steve Bamisile; Muhammad Musa Khan; Waqar Islam; Muhammad Hafeez; Imran Bodlah; Yijuan Xu (Environmental Science and Pollution Research, 2021)

Analysis of income inequality and environmental pollution in BRICS using fresh asymmetric approach - Weijun Zhao; Muhammad Hafeez; Adnan Maqbool; Sana Ullah; Sidra Sohail (Environmental Science and Pollution Research, 2021)

Sublethal concentrations of clothianidin affect fecundity and key demographic parameters of the chive maggot, Bradysia odoriphaga - Hina Gul; Farman Ullah; Muhammad Hafeez; Kaleem Tariq; Nicolas Desneux; Xiwu Gao; Dunlun Song (Ecotoxicology, 2021)

Emamectin benzoate induced enzymatic and transcriptional alternation in detoxification mechanism of predatory beetle Paederus fuscipes (Coleoptera: Staphylinidae) at the sublethal concentration - Muhammad Musa Khan; Aamir Hamid Khan; Muhammad Waqar Ali; Muhammad Hafeez; Shahbaz Ali; Cailian Du; Zeyun Fan; Muzammil Sattar; Hongxia Hua (Ecotoxicology, 2021)

The role of financial development indicators in sustainable development-environmental degradation nexus - Xiaolong Li; Zhiyuan Yu; Asma Salman; Qaisar Ali; Muhammad Hafeez; Muhammad Shoaib Aslam (Environmental Science and Pollution Research, 2021)

Supercooling capacity and cold tolerance of the South American tomato pinworm, Tuta absoluta, a newly invaded pest in China - Xiao-wei Li; Dong Li; Zhi-jun Zhang; Jun Huang; Jin-ming Zhang; Muhammad Hafeez; Li-kun Wang; Wen-chao Guo; Yao-bin Lu (Journal of Pest Science, 2021)
Tuta absoluta is a devastating invasive pest worldwide, causing severe damage to the global tomato industry. It has been recorded recently in the northwestern border areas of China, posing a significant threat to tomato production. It was presumed that the region's winter-related low temperatures would avert the alien species from successfully overwintering. In this study, the supercooling capacity and low-temperature tolerance of this pest were examined under laboratory conditions and its overwintering potential in Xinjiang was estimated. The results showed that the lowest supercooling point was recorded in the adult stage (− 19.47 °C), while the highest (− 18.11 °C) was recorded in the pupal stage. The supercooling points of pupae and adults were not influenced by gender. The Ltemp 50 and Ltemp 90 of female and male adults were the lowest when exposed to cold for 2 h. However, when the duration of exposure extended from 4 to 10 h, the Ltemp 50 and Ltemp 90 of female and male pupae were the lowest. Comparison of the lowest Ltemp 50 and Ltemp 90 with temperatures in January indicated that T. absoluta might not be able to overwinter in most of the northern and central regions of Xinjiang. However, in the southern regions, the extremely low temperature was higher than the Ltemp 90 , suggesting that T. absoluta has a higher overwintering potential in these regions. These results form a basis for predicting the dispersal potential and possible geographic range of this pest in Xinjiang. In addition, our findings provide guidance for the control of this pest by reducing overwintering shelters.

Dusky cotton bug Oxycarenus hyalinipennis Costa (Lygaeidae: Hemiptera) loss assessment in cotton - Faisal Hafeez; Muhammad Akram; Muhammad Farooq; Muhammad Saghir; Muhammad Arshad; Ayesha Iftikhar; Afifa Naeem; Unsar Naeem-Ullah (International Journal of Tropical Insect Science, 2021)

Elucidation of larvicidal potential of metallic and environment friendly food-grade nanostructures against Aedes albopictus - Toqeer Ahmed; Irfan Liaqat; Muhammad Zeeshan Hyder; Shaheen Akhtar; Assad Hafeez Bhatti; Shahid Bilal Butt; Zahid Imran; Tayyaba Yasmin; Shabbar Abbas (Environmental Geochemistry and Health, 2021)

Examining the asymmetric effects of Pakistan’s fiscal decentralization on economic growth and environmental quality - Xiaolong Li; Muhammad Zeeshan Younas; Zubaria Andlib; Sana Ullah; Sidra Sohail; Muhammad Hafeez (Environmental Science and Pollution Research, 2021)

Issue of Accumulation and Redistribution of Oil and Gas Rental Income in the Context of Exhaustible Natural Resources in Arctic Zone of Russian Federation - Natalia Kirsanova; Olga Lenkovets; Muhammad Hafeez (Journal of Marine Science and Engineering, 2020)
The significant resource potential of the Arctic has attracted the attention of its adjacent countries and extra-regional states. The mineral and raw material base of the Arctic Zone of the Russian Federation (AZRF) comprises a wide range of minerals. However, due to its hydrocarbon reserves, the Arctic is considered to be the most important geopolitical and geo-economic macro-region for Russia. A significant portion of the Arctic hydrocarbons (about 19%) is concentrated in the territory of Russia’s shelf. The extraction of Arctic marine oil and gas resources and ensuring the sustainability of the Russian energy complex depend significantly on the level of Arctic development. Thus, the pace and quality of the development of AZRF are strategically important to ensure the national interests of the country. It has been proven that the implementation of the state program for AZRF development and strategic plans of the largest companies operating in the region consolidate the raw material nature of AZRF development. Rent becomes the main form of income. This article addresses the main directions of the region’s development and the factors that prevent a high level of industrialization, which increase attention to the withdrawal and redistribution of rental income. The article considers the Russian and foreign experiences of withdrawal and redistribution of oil and gas rental income, and analyzes the level of socio-economic development of AZRF. The authors suggest a methodology for assessing the impact of a country’s area and population size on the ability to achieve a high income due to hydrocarbons. The authors also explain the principles of rental income redistribution in the region as a basis for improving the level of AZRF’s socio-economic development and as a condition for transition from the “colonial model” of development to the “sustainable development” model. The study results can be used to elaborate a mechanism for rental income redistribution in AZRF and state programs for the region’s development.

Morpho-physiological Effects and Molecular Mode of Action of Mepiquat Chloride Application in Cotton: A Review - Shahbaz Atta Tung; Ying Huang; Abdul Hafeez; Saif Ali; Anda Liu; Muhammad Sohaib Chattha; Shoaib Ahmad; Guozheng Yang (Journal of Soil Science and Plant Nutrition, 2020)

Molecular identification of sugarcane black bug (Cavelarius excavates) from Pakistan using cytochrome C oxidase I (COI) gene as DNA barcode - Khadim Hussain; Kamran Rashid; Faisal Hafeez; Ikrma Amad; Muhammad Ashraf (International Journal of Tropical Insect Science, 2020)

The comparative analysis of essential nutrient fractions in permafrost and different land use systems of Diamer Division, Gilgit-Baltistan - Didar Ahmad; Farhan Hafeez; Muhammad Irshad; Qaisar Mehmood; Adnan Ahmed Tahir; Akhtar Iqbal; Faridullah (Arabian Journal of Geosciences, 2020)

Green purchase behavior towards green housing: an investigation of Bangladeshi consumers - Israt Zahan; Shuai Chuanmin; Madiha Fayyaz; Muhammad Hafeez (Environmental Science and Pollution Research, 2020)

Foliage application and seed priming with nitric oxide causes mitigation of salinity-induced metabolic adversaries in broccoli (Brassica oleracea L.) plants - Nudrat Aisha Akram; Naima Hafeez; Muhammad Farid-ul-Haq; Abrar Ahmad; Muhammad Sadiq; Muhammad Ashraf (Acta Physiologiae Plantarum, 2020)

Biofortification with Zinc and Iron Improves the Grain Quality and Yield of Wheat Crop - Yasir Ramzan; Muhammad Bilal Hafeez; Shahbaz Khan; Majid Nadeem; Saleem-ur-Rahman; Sumaira Batool; Javed Ahmad (International Journal of Plant Production, 2020)

Correction to: Sublethal effects of a juvenile hormone analog, Pyriproxyfen demographic parameters of non-target predator, Hippodamia convergens Guerin-Meneville (Coleoptera: Coccinellidae) - Ayesha Iftikhar; Faisal Hafeez; Muhammad Hafeez; Muhammad Farooq; Muhammad Asif Aziz; Muhammad Sohaib; Afifa Naeem; Yaobin Lu (Ecotoxicology, 2020)

Sublethal effects of a juvenile hormone analog, Pyriproxyfen on demographic parameters of non-target predator, Hippodamia convergens Guerin-Meneville (Coleoptera: Coccinellidae) - Ayesha Iftikhar; Faisal Hafeez; Muhammad Hafeez; Muhammad Farooq; Muhammad Asif Aziz; Muhammad Sohaib; Afifa Naeem; Yaobin Lu (Ecotoxicology, 2020)

The nexus of environmental degradation and technology innovation and adoption: an experience from dragon - Wang Xinmin; Peng Hui; Muhammad Hafeez; Babar Aziz; Muhammad Waqas Akbar; Muhammad Ayzed Mirza (Air Quality, Atmosphere & Health, 2020)

Detection and molecular characterization of Clerodendron yellow mosaic virus infecting Volkameria inermis in Pakistan - Afzal Akram; Aqsa Hafeez Khan; Shahid Mansoor; Peter Moffett; Rob W. Briddon; Muhammad Saeed (Journal of Plant Pathology, 2020)

Codiaeum variegatum in Pakistan harbours pedilanthus leaf curl virus and papaya leaf curl virus as well as a newly identified betasatellite - Afzal Akram; Aqsa Hafeez Khan; Ghulam Rasool; Shahid Mansoor; Peter Moffett; Rob W. Briddon; Muhammad Saeed (Archives of Virology, 2020)

Lipospheres for Simultaneous Controlled Release and Improved Pharmacokinetic Profiles of Saxagliptin-Enalapril: Formulation, Optimization, and Comparative In Vitro-In Vivo Evaluation - Safirah Maheen; Akhtar Rasul; Muhammad Hanif; Hafeez Ullah Khan (AAPS PharmSciTech, 2020)

Downregulation of chitin synthase A gene by diallyl trisulfide, an active substance from garlic essential oil, inhibits oviposition and alters the morphology of adult Sitotroga cerealella - Sakhawat Shah; Muhammad Hafeez; Meng-Ya Wu; Su-Su Zhang; Muhammad Ilyas; Gang Wu; Feng-Lian Yang (Journal of Pest Science, 2020)

Influence of Crapemyrtle aphid, Tinocallis kahawaluokalani (Hemiptera: Aphididae) on population characteristics of three aphidophagous ladybird beetles - Muhammad Asif Aziz; Habiba Sadaf; Ayesha Iftikhar; Faisal Hafeez (International Journal of Tropical Insect Science, 2020)

Inorganic fertilization improves quality and biomass of Moringa oleifera L. - Muhammad Farhan Aslam; Shahzad M. A. Basra; Muhammad Bilal Hafeez; Shahbaz Khan; Sohail Irshad; Shahid Iqbal; Muhammad Sohail Saqqid; Muhammad Zubair Akram (Agroforestry Systems, 2020)

Energy consumption and financial development indicators nexuses in Asian economies: a dynamic seemingly unrelated regression approach - Li Yang; Peng Hui; Rizwana Yasmeen; Sana Ullah; Muhammad Hafeez (Environmental Science and Pollution Research, 2020)

Does regional energy consumption disparities assist to control environmental degradation in OBOR: an entropy approach - Guijuan Sun; Chunhui Yuan; Muhammad Hafeez; Salman Raza; Liu Jie; Xiaodan Liu (Environmental Science and Pollution Research, 2020)

Energy capacity, industrial production, and the environment: an empirical analysis from Pakistan - Muhammad Tariq Mahmood; Sadaf Shahab; Muhammad Hafeez (Environmental Science and Pollution Research, 2020)

Effects of silicon nanoparticles on growth and physiology of wheat in cadmium contaminated soil under different soil moisture levels - Zahra Saeed Khan; Muhammad Rizwan; Muhammad Hafeez; Shafaqat Ali; Muhammad Adrees; Muhammad Farooq Qayyum; Sofia Khalid; Muhammad Zia ur Rehman; Muhammad Aleem Sarwar (Environmental Science and Pollution Research, 2020)

The nexus of fiscal policy instruments and environmental degradation in China - Peng Yuelan; Muhammad Waqas Akbar; Muhammad Hafeez; Manzoor Ahmad; Zeenat Zia; Sana Ullah (Environmental Science and Pollution Research, 2019)

A global prospective of environmental degradations: economy and finance - Muhammad Hafeez; Chunhui Yuan; Qiuyan Yuan; Zhang Zhuo; David Stromaier; Almalki Sultan Musaad O (Environmental Science and Pollution Research, 2019)

Impact of biochar prepared from leaves of Populous euphratica on soil microbial activity and mung bean (Vigna radiata) growth - Muhammad Akmal; Tanveer Ahmed Gondal; Khalid Saifullah Khan; Qaiser Hussain; Mukhtar Ahmad; Muhammad Subtain Abbas; Hafeez Ullah Rafa; Shahab Ahmad Khosa (Arabian Journal of Geosciences, 2019)

An empirical evaluation of financial development-carbon footprint nexus in One Belt and Road region - Muhammad Hafeez; Chunhui Yuan; Khuram Shahzad; Babar Aziz; Kashif Iqbal; Salman Raza (Environmental Science and Pollution Research, 2019)

The accumulation of cadmium in wheat (Triticum aestivum) as influenced by zinc oxide nanoparticles and soil moisture conditions - Zahra Saeed Khan; Muhammad Rizwan; Muhammad Hafeez; Shafaqat Ali; Muhammad Rizwan Javed; Muhammad Adrees (Environmental Science and Pollution Research, 2019)

Does globalization increase the ecological footprint? Empirical evidence from Malaysia - Zahoor Ahmed; Zhaohua Wang; Faisal Mahmood; Muhammad Hafeez; Nazakat Ali (Environmental Science and Pollution Research, 2019)

Sub-lethal effects of lufenuron exposure on spotted bollworm Earias vittella (Fab): key biological traits and detoxification enzymes activity - Muhammad Hafeez; Saad Jan; Muhammad Nawaz; Ehsan Ali; Bahar Ali; Muhammad Qasim; G. Mandela Fernández-Grandon; Muhammad Shahid; Mo Wang (Environmental Science and Pollution Research, 2019)

Glucanolytic Rhizobacteria Produce Antifungal Metabolites and Elicit ROS Scavenging System in Sugarcane - Muhammad Atif Zia; Humaira Yasmin; Faluk Shair; Zahra Jabeen; Saqib Mumtaz; Zafar Hayat; Syed Zia ul Husnain Shah; Shahid Afghan; Fauzia Yusuf Hafeez; Muhammad Nadeem Hassan (Sugar Tech, 2019)

Assessment of flood-induced changes in soil heavy metal and nutrient status in Rajanpur, Pakistan - Farhan Hafeez; Noman Zafar; Rashid Nazir; Hafiz Muhammad Rashad Javeed; Muhammad Rizwan; Faridullah; Saeed Ahmad Asad; Akhtar Iqbal (Environmental Monitoring and Assessment, 2019)

Integrated use of biochar and compost to improve soil microbial activity, nutrient availability, and plant growth in arid soil - Muhammad Akmal; Zubaira Maqbool; Khalid Saifullah Khan; Qaiser Hussain; Shahzada Sohail Ijaz; Muhammad Iqbal; Irfan Aziz; Amjad Hussain; Muhammad Subtain Abbas; Hafeez Ullah Rafa (Arabian Journal of Geosciences, 2019)

Fractionation of heavy metals in contaminated soil after amendment with composted cow manure and poultry litter - Bushra Haroon; Muhammad Irshad; Farhan Hafeez; Arshid Pervez; Faridullah (Arabian Journal of Geosciences, 2019)

Tracing the trade–pollution nexus in global value chains: evidence from air pollution indicators - Rizwana Yasmeen; Yunong Li; Muhammad Hafeez (Environmental Science and Pollution Research, 2019)

Promoter variations in a homeobox gene, BnA10.LMI1, determine lobed leaves in rapeseed (Brassica napus L.) - Limin Hu; Hao Zhang; Qingyong Yang; Qingwei Meng; Shaoqing Han; Chinedu Charles Nwafor; Muhammad Hafeez Ullah Khan; Chuchuan Fan; Yongming Zhou (Theoretical and Applied Genetics, 2018)

Role of Zinc–Lysine on Growth and Chromium Uptake in Rice Plants under Cr Stress - Afzal Hussain; Shafaqat Ali; Muhammad Rizwan; Muhammad Zia ur Rehman; Amjad Hameed; Farhan Hafeez; Saud A. Alamri; Mohammed Nasser Alyemeni; Leonard Wijaya (Journal of Plant Growth Regulation, 2018)

The trade-environment nexus in light of governance: a global potential - Rizwana Yasmeen; Yunong Li; Muhammad Hafeez; Haseeb Ahmad (Environmental Science and Pollution Research, 2018)

Testing EKC hypothesis with energy and sustainable development challenges: a fresh evidence from belt and road initiative economies - Abdul Rauf; Xiaoxing Liu; Waqas Amin; Ilhan Ozturk; Obaid Ur Rehman; Muhammad Hafeez (Environmental Science and Pollution Research, 2018)

Factors hindering the implementation of surgical site infection control guidelines in the operating rooms of low-income countries: a mixed-method study - Muhammad Nasir Ayub Khan; Daniëlle M. L. Verstegen; Abu Bakar Hafeez Bhatti; Diana H. J. M Dolmans; Walther Nicolaas Anton van Mook (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

A field study investigating the potential use of phosphorus combined with organic amendments on cadmium accumulation by wheat and subsequent rice - Muhammad Zia ur Rehman; Muhammad Rizwan; Shafaqat Ali; Asif Naeem; Balal Yousaf; Guijian Lui; Hinnan Khalid; Saifullah; Farhan Hafeez; Muhammad Azhar (Arabian Journal of Geosciences, 2018)

Effect of coal and wood ash on phosphorus immobilization in different textured soils - Muhammad Irshad; Farhan Hafeez; Madiha Naseem; Muhammad Rizwan; Mohammad I. Al-Wabel (Arabian Journal of Geosciences, 2018)

Prevalence of selected pharmaceuticals in surface water receiving untreated sewage in northwest Pakistan - Aisha Khan; Dilawar Farhan Shams; Waliullah Khan; Aamir Ijaz; Muhammad Qasim; Maryam Saad; Ayesha Hafeez; Shams Ali Baig; Nisar Ahmed (Environmental Monitoring and Assessment, 2018)

Association of detoxification enzymes with butene-fipronil in larvae and adults of Drosophila melanogaster - Muhammad Shahid Arain; Muhammad Shakeel; Mohammed Esmail Abdalla Elzaki; Muhammad Farooq; Muhammad Hafeez; Muhammad Rafiq Shahid; Syed Ali Haider Shah; Fawad Zafar Ahmad Khan; Qaiser Shakeel; Abdalla Markaz Abdalla Salim; Guo-Qing Li (Environmental Science and Pollution Research, 2018)

Does finance affect environmental degradation: evidence from One Belt and One Road Initiative region? - Muhammad Hafeez; Yuan Chunhui; David Strohmaier; Manzoor Ahmed; Liu Jie (Environmental Science and Pollution Research, 2018)

Physiological responses of wheat to drought stress and its mitigation approaches - Zahoor Ahmad; Ejaz Ahmad Waraich; Sajjad Akhtar; Shazia Anjum; Tanveer Ahmad; Wajid Mahboob; Osama Bin Abdul Hafeez; Terence Tapera; Maryke Labuschagne; Muhammad Rizwan (Acta Physiologiae Plantarum, 2018)

Beating cold by being tough: impact of elevation on leaf characteristics in Phleum himalaicum Mez. endemic to Himalaya - Khawaja Shafique Ahmad; Mansoor Hameed; Abdul Hamid; Fahim Nawaz; Bushra Hafeez Kiani; Muhammad Sajid Aqeel Ahmad; Jiabin Deng; Farooq Ahmad; Imtiaz Hussain; Sana Fatima (Acta Physiologiae Plantarum, 2018)

Growth promoting potential of fresh and stored Moringa oleifera leaf extracts in improving seedling vigor, growth and productivity of wheat crop - Shahbaz Khan; Shahzad Maqsood Ahmed Basra; Irfan Afzal; Muhammad Nawaz; Hafeez Ur Rehman (Environmental Science and Pollution Research, 2017)

Bacillus safensis with plant-derived smoke stimulates rice growth under saline conditions - Muhammad Hafeez Ullah Khan; Jabar Zaman Khan Khattak; Muhammad Jamil; Ijaz Malook; Shahid Ullah Khan; Mehmood Jan; Ismail Din; Shah Saud; Muhammad Kamran; Hesham Alharby; Shah Fahad (Environmental Science and Pollution Research, 2017)

Biochar soil amendment on alleviation of drought and salt stress in plants: a critical review - Shafaqat Ali; Muhammad Rizwan; Muhammad Farooq Qayyum; Yong Sik Ok; Muhammad Ibrahim; Muhammad Riaz; Muhammad Saleem Arif; Farhan Hafeez; Mohammad I. Al-Wabel; Ahmad Naeem Shahzad (Environmental Science and Pollution Research, 2017)

Soil compaction effects on soil health and cropproductivity: an overview - Adnan Noor Shah; Mohsin Tanveer; Babar Shahzad; Guozheng Yang; Shah Fahad; Saif Ali; Muhammad Adnan Bukhari; Shahbaz Atta Tung; Abdul Hafeez; Biangkham Souliyanonh (Environmental Science and Pollution Research, 2017)

Optimizing the phosphorus use in cotton by using CSM-CROPGRO-cotton model for semi-arid climate of Vehari-Punjab, Pakistan - Asad Amin; Wajid Nasim; Muhammad Mubeen; Muhammad Nadeem; Liaqat Ali; Hafiz Mohkum Hammad; Syeda Refat Sultana; Khawar Jabran; M. Habib ur Rehman; Shakeel Ahmad; Muhammad Awais; Atta Rasool; et al. (Environmental Science and Pollution Research, 2017)

Plant growth promoting rhizobacteria suppress blast disease caused by Pyricularia oryzae and increase grain yield of rice - Afroz Rais; Muhammad Shakeel; Fauzia Yusuf Hafeez; Muhammad Nadeem Hassan (BioControl, 2016)

Cadmium stress in rice: toxic effects, tolerance mechanisms, and management: a critical review - Muhammad Rizwan; Shafaqat Ali; Muhammad Adrees; Hina Rizvi; Muhammad Zia-ur-Rehman; Fakhir Hannan; Muhammad Farooq Qayyum; Farhan Hafeez; Yong Sik Ok (Environmental Science and Pollution Research, 2016)

A Novel Approach Based on Data Redundancy for Feature Extraction of EEG Signals - Hafeez Ullah Amin; Aamir Saeed Malik; Nidal Kamel; Muhammad Hussain (Brain Topography, 2016)

Suppression of red rot disease by Bacillus sp. based biopesticide formulated in non-sterilized sugarcane filter cake - Muhammad Nadeem Hassan; Namood-e-Sahar; Syed Zia-Ul-Husnain Shah; Shahid Afghan; Fauzia Yusuf Hafeez (BioControl, 2015)

Solvent Effect on the Photolysis of Riboflavin - Iqbal Ahmad; Zubair Anwar; Sofia Ahmed; Muhammad Ali Sheraz; Raheela Bano; Ambreen Hafeez (AAPS PharmSciTech, 2015)

Characterization of Reactive Red-120 Decolorizing Bacterial Strain Acinetobacter junii FA10 Capable of Simultaneous Removal of Azo Dyes and Hexavalent Chromium - Faiza Anwar; Sabir Hussain; Shahla Ramzan; Farhan Hafeez; Muhammad Arshad; Muhammad Imran; Zahid Maqbool; Naila Abbas (Water, Air, & Soil Pollution, 2014)

Correction for Irrelevant Absorption in Multicomponent Spectrophotometric Assay of Riboflavin, Formylmethylflavin, and Degradation Products: Kinetic Applications - Iqbal Ahmad; Kiran Qadeer; Kefi Iqbal; Sofia Ahmed; Muhammad Ali Sheraz; Syed Abid Ali; Tania Mirza; Ambreen Hafeez (AAPS PharmSciTech, 2013)

Eggs Distribution Behaviour of Dubas Bug (Ommatissus Lybicus: Homoptera: Tropiduchidae) in Relation to Seasons and Some Physico- Morphic Characters of Date Palm Leaves - Arif Shah; Ata Ul Mohsin; Zahid Hafeez; Muhammad Naeem; Muhammad Irfan Ul Haq (Journal of Insect Behavior, 2013)

Zinc nutrition in rice production systems: a review - Hafeez-ur Rehman; Tariq Aziz; Muhammad Farooq; Abdul Wakeel; Zed Rengel (Plant and Soil, 2012)

Molecular characterization of the modular chitin binding protein Cbp50 from Bacillus thuringiensis serovar konkukian - Muhammad Aamer Mehmood; Xiang Xiao; Fauzia Yusuf Hafeez; Yingbao Gai; Fengping Wang (Antonie van Leeuwenhoek, 2011)

Evaluating surface drying and re-drying for wheat seed priming with polyamines: effects on emergence, early seedling growth and starch metabolism - Muhammad Farooq; Tariq Aziz; Hafeez ur Rehman; Atique ur Rehman; Sardar Alam Cheema; Tariq Aziz (Acta Physiologiae Plantarum, 2011)

Molecular characterization of an endochitinase from Bacillus thuringiensis subsp. konkukian - Muhammad Aamer Mehmood; Xiang Xiao; Fauzia Yusuf Hafeez; Yingbao Gai; Fengping Wang (World Journal of Microbiology and Biotechnology, 2010)

Erratum to: Suppression of red rot caused by Colletotrichum falcatum on sugarcane plants using plant growth-promoting rhizobacteria - Muhammad Nadeem Hassan; Shahid Afghan; Fauzia Yusuf Hafeez (BioControl, 2010)

Suppression of red rot caused by Colletotrichum falcatum on sugarcane plants using plant growth-promoting rhizobacteria - Muhammad Nadeem Hassan; Shahid Afghan; Fauzia Yusuf Hafeez (BioControl, 2010)

Purification and characterization of a chitinase from Serratia proteamaculans - Muhammad Aamer Mehmood; Xiang Xiao; Fauzia Yusuf Hafeez; Yingbao Gai; Fengping Wang (World Journal of Microbiology and Biotechnology, 2009)

Seroprevalence of Toxoplasma gondii in sheep and goats in Rahim Yar Khan (Punjab), Pakistan - M. Ramzan; M. Akhtar; F. Muhammad; I. Hussain; E. Hiszczyńska-Sawicka; A. U. Haq; M. S. Mahmood; M. A. Hafeez (Tropical Animal Health and Production, 2009)